2010
DOI: 10.1016/s1658-3655(12)60016-8
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in Gram-negative pathogenic bacteria in hospitals’ drain in Al-Madina Al-Munnawara

Abstract: Twelve final effluent samples from four hospitals namely Al-Ansar, Al-Miqat, Al-Zahraa and Al-Dar in Al-Madina Al-Munnawara were collected in spring of 2007 and screened for bacterial counts. Gramnegative rods belonging to 21 different species and 13 genera represented the main bulk (65.2%) out of the 359 bacterial isolates followed by Gram-positive rods (31.8%) and Gram positive cocci (3.1%). The most common isolates were belonging to Escherichia coli (32.05%) followed by Enterobacter cloacae (17.9%). The 234… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Brennan and Everman [21] found reduced susceptibility by E. coli isolated from sewage in treatment facilities in Oklahoma which attributed to the accumulation of resistant genes in the environment. Similar studies have reported high occurrence of antibiotic resistant bacteria [22][23][24][25][26]. All the authors revealed high burden of clinically significant antibiotic resistant bacteria (ARB), most with multi-drug resistant ability and tagged the ARB as "environmental pollutants".…”
Section: Introductionmentioning
confidence: 58%
“…Brennan and Everman [21] found reduced susceptibility by E. coli isolated from sewage in treatment facilities in Oklahoma which attributed to the accumulation of resistant genes in the environment. Similar studies have reported high occurrence of antibiotic resistant bacteria [22][23][24][25][26]. All the authors revealed high burden of clinically significant antibiotic resistant bacteria (ARB), most with multi-drug resistant ability and tagged the ARB as "environmental pollutants".…”
Section: Introductionmentioning
confidence: 58%
“…Based on the findings shown in Table 3, it was concluded that E. coli 0157:H7 and Salmonella Typhimurium were the least susceptible to the chile pepper extracts. This was expected, because both bacteria are contain an additional outer cell membrane and are generally more resistant to antimicrobials (Ibrahim et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Resistance to antimicrobial agents is an increasing global problem as it poses a threat to humans [17,33]. Resistant bacteria could colonize vegetables for a number of reasons; the direct use of antimicrobials during cultivation of crops, the use of contaminated animal's manure and irrigation with contaminated water en-route to the fork (consumer) [5].…”
Section: Antibiotic Susceptibilitymentioning
confidence: 99%
“…Drug-resistant infections have profound health consequences for the most vulnerable populace including patients, children, the elderly people, pregnant women as well as lactating mothers [15]. The problem of antibiotic resistance is not restricted to Ghana only but it is worldwide and the World Health Organization (WHO) in the year 2000 hinted of the world reaching a crisis point in relation to the level of resistance of microbes to drugs used in treating common infectious diseases [16,17]. Antibacterial resistance involves bacteria that cause many common and life threatening infections as there are available literature showing that much of the problem of infectious diseases worldwide result from antimicrobial-resistant bacteria and more virulent strains of such pathogenic microbes have evolved [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%